THE EFFECT OF ACCEPTANCE AND COMMITMENT THERAPY ON ALEXITHYMIA, RUMINATION, AND LONELINESS DURING BREAST CANCER TREATMENT - Parisa Siyahmansuri; Sara Hashemi (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
This study aimed to determine the effectiveness of acceptance and commitment therapy on alexithymia, rumination, and loneliness in breast cancer patients. A quasi-experimental pre-test and post-test were conducted in 2021 with experimentation, control, and follow-up groups. This study included women with breast cancer who had been treated in public hospitals in Tehran's District 2 for at least two years and had been referred to them. To determine the effectiveness of the experiment and control groups, 30 participants were randomly selected by purposive sampling. The Toronto alexithymia scale, the Nolan, Hoxma, & Murrow (1991) rumination scale, and the Russell UCLA Loneliness Scale (1996) were used to evaluate subjects before and after the intervention. Group acceptance and commitment therapy was administered to the experimental group in eight sessions of 90 minutes once a week. The data was analyzed two months after the last treatment session using covariance analysis. Based on the analysis of covariance, it was demonstrated that alexithymia and rumination significantly differed between the experimental and control groups. However, there was no significant difference between the experimental and control groups in loneliness (P>0.05). Despite the effectiveness of acceptance and commitment therapy in treating alexithymia and rumination in women with breast cancer, this intervention could not affect the feeling of loneliness among these women